Funding for lending schemes should prioritize SME lending - Barnabás Székely (Magyar Nemzeti Bank, 2020)
In the aftermath of the sovereign debt crisis the Central Bank of Hungary implemented a great-scale funding for lending scheme designed specifically to subsidize SME finance. This creates a unique opportunity to identify this policy in the SVAR framework as asymmetric credit supply shocks specific to SME lending. I find that during the post-crisis recovery, such disturbances had a substantial effect on lending conditions and the real economy. Moreover, rather than supplanting lending to large enterprises, the program had considerable positive spillover effects to this sector. Finally, for a unit of lending, these shocks had larger and more persistent effect on output than general credit supply shocks. These results are robust to different proxies of economic performance and alternative identification strategies. I conclude that under tight lending conditions funding for lending schemes are more effective if concentrated to SMEs.
Keywords: C11; E32; E44; E58; 330; Bayesian SVARs; Credit supply shocks; Funding for lending scheme; SME finance